Bridging the Intention-Behavior Gap? : The Effect of Plan-Making Prompts on Job Search and Employment - Abel, Martin; Piraino, Patrizio; Burger, Rulof; Carranza, Eliana; Piraino, Patrizio (World Bank, Washington, DC, 2017)
The paper tests the effects of plan-making on job search and employment. In a field experiment with unemployed youths, participants who complete a detailed job search plan increase the number of job applications submitted (by 15 percent) but not the time spent searching, consistent with intention-behavior gaps observed at baseline. Job seekers in the plan-making group diversify their search strategy and use more formal search channels. This greater search efficiency and effectiveness translate into more job offers (30 percent) and employment (26 percent). Weekly reminders and peer-support sub-treatments do not improve the impacts of plan-making, suggesting that limited attention and accountability are unlikely mechanisms.